The Sacred Basileía of Justinian (527–565): Concept, Definitions, and Problems - de Oliveira, Ana Maria (Romanitas - Revista de Estudos Grecolatinos, 2026)
Most of the historiography on Byzantium maintains that the political model employed by Justinian in the sixth century was an autocracy. Conceptual definitions of the term, however, are generally restricted to texts that, in essence, trace its origin to the title autokrátōr, drawn from the official protocols of the imperial chancery and used to denote a centralizing and unlimited power, as Justinian’s administration is understood to have been according to this line of interpretation. These historiographical assertions, however, diverge from the Greek texts of the panegyrics On Buildings and Description of Hagia Sophia, written respectively by Procopius of Caesarea (490–562) and Paul the Silentiary (?-580), which employ the form of address basileús. On the basis of these two authors, we seek to propose, as an alternative explanatory framework, the concept of sacred basileía, considering its use primarily as a means of articulating the divine assistance granted to Justinian in his exercise of rule.